Assessing Labor Wage Systems in Companies from an Islamic Legal Perspective - Nasruddin Yusuf; Fahrurrazi Ibrahim; Fathum Ibrahim (Fakultas Hukum Dehasen, 2024)
This study aims to examine the wage system at CV Bregas, located in Desa Maen Likupang Timur, and assess its compliance with Islamic economic law principles. This field research, conducted at IAIN Manado, employs a qualitative approach grounded in juridical legal methods to study natural objects. Data was collected through interviews, observations, and documentation, and analyzed using an interactive model that includes data reduction, data presentation, and conclusion drawing. The findings reveal that CV Bregas, owned by Mr. Karmin, implements a wage system with variations in daily, weekly, and monthly wages. Monthly and daily wages exceed the UMP of North Sulawesi Province and the UMK of the relevant regency/city, while weekly wages fall below these standards. The wage mechanism is based on agreements between workers and company management. The wage system at CV Bregas is deemed compliant with Islamic economic law, as wage determination is based on mutual consent, payments are made after work completion, and disputes are resolved primarily through deliberation.